2016
DOI: 10.1192/bjpo.bp.115.002808
|View full text |Cite
|
Sign up to set email alerts
|

The association between borderline personality disorder, fibromyalgia and chronic fatigue syndrome: systematic review

Abstract: BackgroundOverlap of aetiological factors and demographic characteristics with clinical observations of comorbidity has been documented in fibromyalgia syndrome, chronic fatigue syndrome (CFS) and borderline personality disorder (BPD).AimsThe purpose of this study was to assess the association of BPD with fibromyalgia syndrome and CFS. The authors reviewed literature on the prevalence of BPD in patients with fibromyalgia or CFS and vice versa.MethodsA search of five databases yielded six eligible studies. A ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“… 1 A recent systematic review of the literature dedicated to the association of BP disorder with fibromyalgia and chronic fatigue syndrome—two conditions that can be considered close to burnout—concluded that more research is required to clarify possible associations between the three entities (Penfold et al, 2016 ). …”
mentioning
confidence: 99%
“… 1 A recent systematic review of the literature dedicated to the association of BP disorder with fibromyalgia and chronic fatigue syndrome—two conditions that can be considered close to burnout—concluded that more research is required to clarify possible associations between the three entities (Penfold et al, 2016 ). …”
mentioning
confidence: 99%
“…The final number of articles enrolled in this study was 24, of which the full texts were examined independently. We decided to exclude a review about borderline personality disorder [ 31 ] in fibromyalgia because of its focus on a specific psychopathological disorder, a meta-analysis about the use of Minnesota Multiphasic Personality Inventory (MMPI) [ 22 ] in patients with fibromyalgia for its focus on a specific instrument and, lastly, a letter to the editor about perfectionism [ 32 ]. The articles examined for this systematic review were definitively 21.…”
Section: Methodsmentioning
confidence: 99%
“…However, the failure to identify an infectious agent, find any standard, disease-specific, clinical laboratory abnormality in these patients, along with the occurrence of many, apparently, “isolated,” cases, have led a component of the healthcare community to be doubtful of a physiological cause of the disease. Often these studies conclude that the illness is psychological or psychosomatic in nature (Penfold, St. Denis, & Mazha, 2016). For years, studies have been published demonstrating the psychological or psychosomatic causation of ME/CFS (Penfold et al).…”
Section: Cause Of Me/cfs and The Controversymentioning
confidence: 99%
“…Often these studies conclude that the illness is psychological or psychosomatic in nature (Penfold, St. Denis, & Mazha, 2016). For years, studies have been published demonstrating the psychological or psychosomatic causation of ME/CFS (Penfold et al). More recently, the data analyses used in these studies have been questioned calling for the withdrawal of these papers (Rehmeyer & Tuller, 2017; Wilshire et al, 2018).…”
Section: Cause Of Me/cfs and The Controversymentioning
confidence: 99%